Economic Valuation of Fortified Cassava Peels for Goat Feeding in South-western, Nigeria - L. O, Okojie; Adewuyi , S. A; K, Adebayo; A. M, Adetoye (Asian Journal of Agriculture and Rural Development, 2014)
This paper investigates the economic value that goat farmers in South-western, Nigeria attach to fortified goat feed from waste cassava peels origin. Unavailability of vegetative forage for goat feeding all year round makes this relevant. A multistage sampling procedure was used to select 120 goat farmers. Primary data for the study were obtained with the aid of structured questionnaire. The method of analysis included descriptive statistics and contingent valuation method that terminated into the binary choice logit model. The study indicates the mean Willingness to Pay (WTP) for a 25kg of fortified goat feed as N1, 019: = in the study area. This for the 120 sampled farmers was N122, 280: = and for the total population of 7.1million, it was N7.2billion. Respondents’ WTP however increased mainly with level of education and system of goat keeping. Farming system practiced by respondents had the likelihood of positively and significantly (p<0.01) affecting the WTP for fortified goat feed from cassava peels. Income equally had the likelihood of positively and significantly (p<0.05) affecting the WTP in the study area. Education, farm size and experience had the likelihood of positively influencing though not significantly the WTP for the compounded feed. These indicate that there exist economic potentials for the use of cassava waste (peels) in goat production in the study area. Adopting intensive system of goat farming and enhancing income of producers will go a long way to motivating investment in the feed making and its adoption in goat production.